2014
DOI: 10.1093/petrology/egu045
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Blueschist-facies Minerals along a Shear Zone by Coupled Metasomatism and Fast-flowing CO2-bearing Fluids

Abstract: Two types of blue halo (types I and II) composed of blueschist-facies minerals are centered around a brittle, normal shear zone in greenschist-facies rocks on the island of Syros, Aegean Sea, Greece. The shear zone is steeply dipping and cuts a near-horizontal layer of greenschist-facies rocks (albite + epidote + actinolite + chlorite + quartz). Type I and II blue haloes are 0·3 m and c. 1 m wide respectively, and are seen on both sides of the shear zone. The inner type I haloes are composed of nearly pure gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…However, HP–LT mineral assemblages formed due to crustal thickening associated with subduction are often partly or entirely replaced at lower pressure and higher temperature conditions associated with exhumation (Ernst, ). Preservation of HP–LT rocks can reflect an absence of metamorphic fluids (Schliestedt & Matthews, ), restriction of fluid availability to specific P–T conditions (Schorn, ) or fluid composition effects (Breeding, Ague, Bröcker, & Bolton, ; Kleine, Skelton, Huet, & Pitcairn, ). The presence or absence of metamorphic fluids as well as fluid composition effects, usually reflecting channelized fluid flow, provides possible explanations for the occurrence of HP–LT (eclogites and blueschists) rocks in close proximity to rocks that record metamorphism at lower pressure and/or higher temperature (greenschists, amphibolites and granulites) (Austrheim, ; Glodny, Austrheim, Molina, Rusin, & Seward, ; Glodny, Kühn, & Austrheim, ; Glodny, Ring, & Kühn, ; Jun & Klemd, ; Proyer, ; Young & Kylander‐Clark, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HP–LT mineral assemblages formed due to crustal thickening associated with subduction are often partly or entirely replaced at lower pressure and higher temperature conditions associated with exhumation (Ernst, ). Preservation of HP–LT rocks can reflect an absence of metamorphic fluids (Schliestedt & Matthews, ), restriction of fluid availability to specific P–T conditions (Schorn, ) or fluid composition effects (Breeding, Ague, Bröcker, & Bolton, ; Kleine, Skelton, Huet, & Pitcairn, ). The presence or absence of metamorphic fluids as well as fluid composition effects, usually reflecting channelized fluid flow, provides possible explanations for the occurrence of HP–LT (eclogites and blueschists) rocks in close proximity to rocks that record metamorphism at lower pressure and/or higher temperature (greenschists, amphibolites and granulites) (Austrheim, ; Glodny, Austrheim, Molina, Rusin, & Seward, ; Glodny, Kühn, & Austrheim, ; Glodny, Ring, & Kühn, ; Jun & Klemd, ; Proyer, ; Young & Kylander‐Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…vein‐fractures, shear zones); whereas, preservation of HP–LT mineral assemblages occurs in the parts of a rock volume that have been dry (Matthews & Schliestedt, ; Parra, Vidal, & Jolivet, ). Less commonly, metamorphic fluids preserve HP–LT mineral assemblages by maintaining a fluid composition which stabilizes the HP–LT assemblage relative to the replacement assemblage (Kleine et al., ). Despite this important kinetic role played by metamorphic fluids, few systematic studies of the interplay between metamorphic fluid flow and other factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen, Jamtveit, Dewey, & Swensson, ; Hacker, ; Haifler & Kotková, ), how the great depths can be recorded (e.g. O'Brien & Rötzler, ; Ravna & Terry, ) and how the HP and UHP rocks can be preserved on their way back to surface conditions (Austrheim, Erambert, & Engvik, ; Kleine, Skelton, Huet, & Pitcairn, ; Štípská, Powell, & Racek, ). The dynamics in the deep orogenic root have been traced in rocks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…; Kleine et al . ). Zircon morphology provides a sensitive monitor of fluid pathways in crustal rocks capable of recording a range of different interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Other workers have shown that porosity and permeability may be controlled by mineralogy (Arghe et al 2011;Ferry et al 2013), and equilibrium wetting angles (Holness 1993;Price et al 2004), but there are many reports of a structural control of fluid pathways (e.g. Skelton et al 1995;Abart et al 2002;Pitcairn et al 2010;Kleine et al 2014). Zircon morphology provides a sensitive monitor of fluid pathways in crustal rocks capable of recording a range of different interactions.…”
Section: Discussionmentioning
confidence: 99%